Hydrophobic catalyst for water-hydrogen exchange reaction and preparation method thereof
By growing a porous nitrogen-doped carbon layer in situ on a foam nickel support and supporting Pt active components and grafted fluorosilane to form a regular hydrophobic catalyst, the lack of regular catalysts in the prior art is solved, and high catalytic activity, good hydrophobic properties and stability are achieved.
Patent Information
- Application Number
- CN202411805129.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-09
AI Technical Summary
There is a lack of regular catalysts in large-scale industrial applications, resulting in high gas resistance, poor mass and heat transfer ability, and easy slag dropping.
Using nickel foam as a support, a porous nitrogen-doped carbon layer with a porous structure is grown in situ by hydrothermal method, supporting the active component Pt, and grafting fluorosilane as a hydrophobic component on the nitrogen-doped carbon layer to form a regular hydrophobic catalyst.
The catalytic activity and stability of the hydrophobic catalyst are improved, their hydrophobic properties are enhanced, the waste of precious metals is reduced, and the serious problems of heavy support mass and pulverization in the prior art are solved.
Smart Images

Figure BDA0005180266630000111 
Figure BDA0005180266630000121 
Figure BDA0005180266630000122
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a hydrophobic catalyst for water-hydrogen exchange reaction and a preparation method thereof. Background Art
[0002] Among the many hydrogen isotope separation methods, water-hydrogen exchange reaction has been widely used due to its advantages of high separation factor, low energy consumption and low cost. Among them, hydrophobic catalyst is an indispensable part of water-hydrogen exchange reaction. Hydrophobic catalyst is mainly composed of active component and hydrophobic carrier. The hydrophobic catalyst used in current research mainly includes three major types of catalysts: Pt / SDB, Pt / C / PTFE, and Pt / C / inert carrier (Pt / C / IC). Most of these three types of hydrophobic catalysts exist in the form of granular catalysts. However, in large-scale industrial applications, regular catalysts are more advantageous. Regular catalysts have the advantages of low gas resistance, strong mass and heat transfer capacity, and easy to scale up. Therefore, in order to realize the large-scale industrial application of hydrophobic catalysts, it is necessary to develop regular hydrophobic catalysts, that is, to prepare hydrophobic catalysts using regular carriers.
[0003] In the studies reported so far, the structured carriers used are mainly honeycomb ceramic cordierite, nickel foam (FN), and silicon carbide foam (SiC). The literature (Xu M, Zhang S, Wang T, et al. De novo design of aPt nanocatalyst on a conjugated microporous polymer-coated honeycomb carrier for oxidation of hydrogen isotopes [J]. ACS Applied Materials & Interfaces, 2022, 14 (6): 7826-7835.) reported a method for preparing a hydrophobic catalyst using cordierite as a carrier, which is to graft an organic polymer with intrinsic hydrophobicity on its surface, but in this method, the grafting process is cumbersome and the hydrophobicity is poor. The patent (CN107930621A) discloses a method for preparing a hydrophobic catalyst using foamed silicon carbide (SiC) as a carrier. The preparation method is to load polytetrafluoroethylene (PTFE) on the carrier using a natural impregnation method to construct a hydrophobic surface and then load the active component Pt. In this method, the dispersibility of the active component Pt is poor. In addition, foamed silicon carbide (SiC) and cordierite are both ceramic materials, which are heavy and have serious powdering and are easy to fall off.
[0004] Therefore, there is still a need to continue to develop regular hydrophobic catalysts with better comprehensive performance. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a regular hydrophobic catalyst having good catalytic activity.
[0006] To this end, the present invention provides a hydrophobic catalyst for a water-hydrogen exchange reaction, the hydrophobic catalyst comprising: a carrier, the carrier comprising nickel foam and a nitrogen-doped carbon layer grown in situ on the surface of the nickel foam, the nitrogen-doped carbon layer having a porous structure; an active component, the active component being loaded on the nitrogen-doped carbon layer, the active component comprising Pt; and a hydrophobic component, the hydrophobic component being grafted on the nitrogen-doped carbon layer, the hydrophobic component comprising fluorosilane.
[0007] In some embodiments, the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt.
[0008] In some embodiments, the fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane.
[0009] In some embodiments, the loading amount of the active component is 0.1 wt%-1.0 wt% based on the total weight of the carrier.
[0010] A second aspect of the present invention provides a method for preparing a hydrophobic catalyst, comprising the following steps:
[0011] S1, placing a solution including a carbon source and a nitrogen source and nickel foam in a reaction kettle, performing a hydrothermal reaction at 120° C.-180° C. for 4 h-18 h, and then mixing with an alkaline solution for activation treatment to obtain a carrier having a nitrogen-doped carbon layer in situ grown on the surface of the nickel foam;
[0012] S2, impregnating the carrier with a precursor solution of an active component, and performing a reduction reaction after drying to obtain a carrier loaded with an active component, wherein the active component includes Pt;
[0013] S3, immersing the above-mentioned carrier loaded with active components in a solution containing a hydrophobic component for 12h-24h, taking it out and drying it for 6-12h to obtain the hydrophobic catalyst, wherein the hydrophobic component includes fluorosilane.
[0014] In some embodiments, in step S1, the activation treatment comprises reacting with the alkaline solution at 100°C-150°C for 6h-24h, and then calcining at 600°C-800°C for 0.5h-3h in an argon atmosphere.
[0015] In some embodiments, the ratio of the mass of the nitrogen-doped carbon layer to the mass of the alkali in the alkali solution is 1:1-1:3.
[0016] In some embodiments, the base is selected from one or more of KOH or NaOH.
[0017] In some embodiments, in step S1, the carbon source is glucose; and the nitrogen source is urea.
[0018] In some embodiments, in step S2, the precursor solution of the active component is selected from an alcohol solution of chloroplatinic acid, an alcohol solution of ferrous chloride and chloroplatinic acid, an alcohol solution of chloroiridic acid and chloroplatinic acid, and an alcohol solution of ruthenium trichloride and chloroplatinic acid, wherein the alcohol is ethanol or ethylene glycol.
[0019] In some embodiments, the concentration of the precursor solution of the active component is 0.1 mol / L-0.3 mol / L.
[0020] In some embodiments, the active component precursor solution is added in an amount of 0.1-1.0 wt% of the active component loading based on the total weight of the support with the in-situ grown nitrogen-doped carbon layer; the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt.
[0021] In some embodiments, in step S2, the reduction reaction is carried out in an argon atmosphere using hydrogen as a reducing agent, the reaction temperature is 200°C-300°C, and the reaction time is 6h-12h.
[0022] In some embodiments, in step S3, the solution of the hydrophobic component is an ethanol solution of the hydrophobic component; the concentration of the hydrophobic component solution is 0.1 wt%-0.3 wt%.
[0023] In some embodiments, the fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane.
[0024] In the present invention, nickel foam with a nitrogen-doped carbon layer having an in-situ porous structure is used as a carrier to provide a regular hydrophobic catalyst with improved performance, wherein the nitrogen-doped carbon layer provides binding sites for loaded active components, so that the active components can be evenly dispersed on the carrier and fully exposed, thereby improving the utilization rate of the active components, improving the catalytic activity of the hydrophobic catalyst, and reducing the waste of precious metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the grafting principle of the hydrophobic component in the hydrophobic catalyst of the present invention.
[0026] Figure 2The XPS test spectra are of the platinum-loaded catalyst (catalyst before hydrophobic treatment) prepared in step S2 of Example 1 of the present invention and the Pt / NC / FN hydrophobic catalyst (catalyst after hydrophobic treatment) prepared in step S3. DETAILED DESCRIPTION
[0027] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0029] It should be noted that, in the embodiments of the present invention, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other related elements in the method or device including the element.
[0030] It should be noted that the terms "first\second\third" involved in the embodiments of the present invention are only used to distinguish similar objects, and do not represent a specific order for the objects. It is understandable that the specific order or sequence of "first\second\third" can be interchanged where permitted. It should be understood that the objects distinguished by "first\second\third" can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein.
[0031] Nickel foam has the advantages of light weight, low cost, strong processability, strong mass transfer and heat transfer capacity, therefore, nickel foam has greater application potential compared to ceramic materials, and is very suitable for preparing regular hydrophobic catalysts. However, in the prior art, the mode of preparing hydrophobic catalysts with nickel foam as carrier is usually to apply Pt / C / PTFE to nickel foam by natural impregnation method, and active component Pt is loaded on porous carbon to make Pt / C, then Pt / C is mixed with polytetrafluoroethylene (PTFE), Triton to make emulsion, and finally Pt / C / PTFE is loaded on nickel foam by impregnation method to prepare hydrophobic catalyst. For example, it is reported in document " Improved catalysts for hydrogen / deuterium exchange reactions " that PTFE is hydrophobic component, Pt / C powder and PTFE, PMMA, Triton are mixed into suspension, and Pt / C / PTFE is loaded on stainless steel felt by natural impregnation method, and the contact angle measured is 125 °. The hydrophobic catalyst prepared by this method has certain defects, such as Pt is easily covered, resulting in waste of precious metals, Pt / C / PTFE coating is easy to fall off, and PTFE has poor hydrophobicity.
[0032] In view of this, the present invention provides a hydrophobic catalyst, which includes: a carrier, the carrier includes nickel foam and a nitrogen-doped carbon layer grown in situ on the surface of the nickel foam, the nitrogen-doped carbon layer having a porous structure; an active component, the active component is loaded on the nitrogen-doped carbon layer, the active component includes Pt; and a hydrophobic component, the hydrophobic component is grafted on the nitrogen-doped carbon layer, and the hydrophobic component includes fluorosilane.
[0033] In the present invention, the nickel foam with nitrogen-doped carbon layer grown in situ is used as a carrier. On the one hand, since the nitrogen element in the nitrogen-doped carbon layer has a lone electron pair, it can coordinate with the active component, has an anchoring effect on the active component, suppresses the agglomeration of the active component, and is conducive to improving the dispersibility of the active component on the carrier surface. On the other hand, the nitrogen-doped carbon layer in the carrier has a porous structure that is conducive to improving the specific surface area of the hydrophobic catalyst, thereby providing more binding sites to load the active component, thereby improving the catalytic efficiency of the hydrophobic catalyst. The in-situ grown nitrogen-doped carbon layer disperses the active component by its porosity, physical properties such as large specific surface area and chemical coordination of N atoms and active components, so that the active component is highly dispersed on the carrier and the particle size is small, which is conducive to improving the catalytic activity of the catalyst. Further, the active component of the catalyst is closely combined with the nickel foam carrier, and is not easy to fall off during use, thereby improving the stability and service life of the catalyst. In addition, the active component is loaded on the surface of the nitrogen-doped carbon layer in the present invention, so that the active component is fully exposed, the utilization rate of the active component is improved, and the catalytic activity of the hydrophobic catalyst is improved.
[0034] In the present invention, the active component is a catalyst commonly used in water-hydrogen exchange reactions. In the present invention, the active component includes Pt. In some embodiments, the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt. The above active components have good catalytic performance for water-hydrogen exchange reactions.
[0035] In the present invention, the hydrophobic component includes fluorosilane. The term "fluorosilane" refers to a silane containing -CF2 and -CF3 functional groups. Fluorosilane is used as a hydrophobic component, and the -CF2 and -CF3 functional groups in the fluorosilane have extremely low surface energy, and because the nitrogen-doped carbon layer grown in situ on the carrier has a higher roughness, under the combined effect of the higher carrier roughness and the lower surface energy of the hydrophobic component, the catalyst has a super-hydrophobic surface, which is conducive to improving the hydrophobic properties of the hydrophobic catalyst. In addition, hydrophobic components such as fluorosilane can be grafted on the carrier in the form of chemical bond condensation, which belongs to chemical bonding and has a higher stability, which is conducive to improving the service life of the catalyst. In some embodiments, fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane; preferably heptadecafluorodecyltrimethoxysilane.
[0036] In some embodiments, the loading amount of the active component is 0.1wt%-1.0wt% based on the total weight of the carrier. The loading amount of the active component beyond the above range is likely to cause the active component to agglomerate, thereby reducing the catalytic activity; the loading amount of the active component is lower than the above range, so that the content of the active component is less, thereby causing the catalytic activity of the catalyst to be low. By making the loading amount of the active component within the above range, it is beneficial to improve the catalytic efficiency of the hydrophobic catalyst and have good cost-effectiveness. Exemplarily, based on the total weight of the hydrophobic catalyst, the loading amount of the active component can be 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt% or a value between the ranges consisting of any two of them.
[0037] Another aspect of the present invention provides a method for preparing a hydrophobic catalyst, the method comprising the following steps:
[0038] S1, placing a solution including a carbon source and a nitrogen source and nickel foam in a reaction kettle, performing a hydrothermal reaction at 120° C.-180° C. for 4 h-18 h, and then mixing with an alkaline solution for activation treatment to obtain a carrier having a nitrogen-doped carbon layer in situ grown on at least a portion of the surface of the nickel foam;
[0039] S2, impregnating the carrier with a precursor solution of an active component, and performing a reduction reaction after drying to obtain a carrier loaded with an active component, wherein the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt;
[0040] S3, immersing the above-mentioned carrier loaded with active components in a solution containing a hydrophobic component for 12h-24h, taking it out and drying it for 6-12h to obtain the hydrophobic catalyst, wherein the hydrophobic component includes fluorosilane.
[0041] In the present invention, step S1 grows nitrogen-doped carbon in situ on nickel foam by a hydrothermal method, so that the nitrogen-doped carbon layer is tightly combined with the nickel foam matrix, avoiding the use of a binder, which is beneficial to improving the stability and service life of the catalyst. The hydrothermal reaction is carried out at 120°C-180°C for 4h-18h. This is beneficial to convert the carbon source and the nitrogen source into nitrogen-doped carbon. Exemplarily, the temperature of the hydrothermal reaction can be 120°C, 140°C, 160°C, 180°C or a value between the ranges consisting of any two of them; the reaction time can be 4h, 6h, 8h, 10h, 12h or a value between the ranges consisting of any two of them.
[0042] In some embodiments, the carbon source is glucose and the nitrogen source is urea. The above raw materials are widely available and inexpensive, which is conducive to saving the preparation cost of the hydrophobic catalyst.
[0043] In some embodiments, in step S1, before the activation treatment, the product obtained by the hydrothermal reaction is washed and dried. For example, the nickel foam loaded with nitrogen-doped carbon obtained after the hydrothermal reaction is taken out, rinsed with deionized water for 3-4 times, and then dried at 60-100° C. overnight.
[0044] In step S1, after the above-mentioned hydrothermal reaction is completed, the prepared nickel foam with an in-situ grown nitrogen-doped carbon layer is activated by an alkaline solution to form a nitrogen-doped carbon layer with a porous structure, which increases the active sites on the carrier surface for binding to the active components, increases the loading amount of the active components, and is beneficial to the uniform dispersion of the active components on the carrier surface, thereby improving the catalytic activity of the catalyst.
[0045] In some embodiments, the activation treatment comprises reacting the mixture of the product obtained by the hydrothermal reaction and the alkaline solution at 100°C-150°C for 6-24h, and then calcining at 600-800°C for 0.5h-3h in an argon atmosphere. The mixture of the nickel foam with the nitrogen-doped carbon layer grown in situ obtained by the hydrothermal reaction and the alkaline solution is reacted at 100°C-150°C for 6-24h, so that the alkali reacts fully with the nitrogen-doped carbon layer on the nickel foam to form a porous structure, and then calcining at 600-800°C for 0.5-3h in an argon atmosphere to fully activate the nitrogen-doped carbon layer, so as to facilitate the subsequent loading of active components and grafting of hydrophobic components.
[0046] In some embodiments, the base is selected from one or more of KOH and NaOH. The base can fully react with the nitrogen-doped carbon layer on the nickel foam to release gas and form a porous structure.
[0047] In some embodiments, the ratio of the mass of the nitrogen-doped carbon layer supported on the nickel foam to the mass of the alkali in the alkaline solution is 1:1-1:3. By making the ratio of the mass of the nitrogen-doped carbon layer to the mass of the alkali within the above range, it is beneficial for the alkali to fully react with the nitrogen-doped carbon. Exemplarily, the mass of the nitrogen-doped carbon layer grown in situ on the nickel foam can be obtained by the difference method, that is, weighing the mass of the nickel foam before the hydrothermal reaction, recorded as M0, and then weighing the mass of the nickel foam with a porous nitrogen-doped carbon layer obtained after the step S1 is completed, recorded as M1, and the mass M of the nitrogen-doped carbon layer on the nickel foam is the difference between M1 and M0.
[0048] In some embodiments, after the activation treatment, the obtained nickel foam with in-situ porous nitrogen-doped carbon layer is washed and dried. For example, the obtained nickel foam with in-situ porous nitrogen-doped carbon layer is washed with deionized water and dried at 100-150° C. for 12-24 hours under vacuum.
[0049] In the present invention, step S2 is to attach the active component precursor to the carrier having the porous nitrogen-doped carbon layer by impregnation, and then perform a reduction reaction after drying to obtain the carrier loaded with the active component. Thus, the active component is fully exposed on the surface of the carrier.
[0050] In some embodiments, the active component precursor solution is selected from an alcohol solution of chloroplatinic acid, an alcohol solution of ferrous chloride and chloroplatinic acid, an alcohol solution of chloroiridic acid and chloroplatinic acid, and an alcohol solution of ruthenium trichloride and chloroplatinic acid, wherein the alcohol is selected from ethanol or ethylene glycol. The above active component precursor solutions can obtain active metals with catalytic activity on the surface of the carrier through a reduction reaction.
[0051] In some embodiments, the concentration of the active component precursor solution is 0.1mol / L-0.3mol / L. By making the concentration of the active component precursor solution in the above range, it is beneficial for the active component to be evenly dispersed on the surface of the carrier, thereby improving the catalytic activity of the hydrophobic catalyst. Exemplarily, the concentration of the active component precursor solution can be 0.1mol / L, 0.2mol / L, 0.3mol / L or a value between the ranges consisting of any two of them.
[0052] In some embodiments, the active component precursor solution is added in an amount of 0.1 wt% to 1.0 wt% of the active component loading based on the total weight of the support having the in-situ grown nitrogen-doped carbon layer, thereby facilitating the regulation of the loading of the active component, thereby improving the catalytic efficiency of the hydrophobic catalyst.
[0053] In some embodiments, the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt.
[0054] In some embodiments, the reduction reaction is performed in an argon atmosphere using hydrogen as a reducing agent.
[0055] In some embodiments, during the reduction reaction, the argon gas flow rate is 400 mL / min-1000 mL / min.
[0056] In some specific embodiments, the reduction reaction includes introducing argon gas, heating the mixture to a reaction temperature at a heating rate of 5-15° C. / min under an argon atmosphere, and then introducing hydrogen gas to start the reduction reaction.
[0057] In some embodiments, the flow ratio of argon to hydrogen is 1:1-1:3. For example, the flow ratio of argon to hydrogen can be 1:1, 1:2, 1:3 or a value between any two ratios thereof.
[0058] In some embodiments, the reaction temperature of the reduction reaction is 200-300° C., and the reaction time is 6-12 hours. By making the reduction reaction meet the above conditions, it is beneficial to increase the content of metal elements in the active component and reduce the particle size of the active component, thereby facilitating the improvement of the catalytic activity of the catalyst.
[0059] In the present invention, step S3 uses an impregnation method to form a grafted hydrophobic layer on the carrier loaded with active components, reducing the surface energy of the carrier, thereby facilitating the hydrophobic catalyst to have good hydrophobic properties, and will not cover the active components, which is conducive to fully exposing the active components and improving the catalytic activity of the hydrophobic catalyst. Through sufficient impregnation for 12h-24h, a large amount of hydrophobic components can be grafted onto the carrier, which is conducive to improving the hydrophobic properties of the hydrophobic catalyst.
[0060] In some embodiments, the hydrophobic component solution is an ethanol solution of the hydrophobic component. This facilitates the uniform dispersion of the hydrophobic component in the solution, so that as many hydrophobic components as possible undergo dehydration condensation reactions with hydroxyl groups on the surface of the carrier, reducing the surface energy of the carrier to make it reach a super-hydrophobic state, improving the hydrophobicity of the catalyst while not covering the active component, thereby improving the catalytic activity.
[0061] In some embodiments, the concentration of the hydrophobic component solution is 0.1wt%-0.3wt%. By using the hydrophobic component solution of the above concentration, it is beneficial to form a hydrophobic layer on the carrier loaded with the active component, thereby improving the hydrophobicity of the catalyst. Exemplarily, the concentration of the hydrophobic component solution can be 0.1wt%, 0.2wt%, 0.3wt% or a value between the ranges consisting of any two of them.
[0062] In some embodiments, the fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane. The fluorosilane reagent hydrolyzes Si-OCH3 into Si-OH by itself, and then the Si-OH obtained by hydrolysis undergoes a dehydration condensation reaction with the -OH on the carrier to graft the fluorosilane reagent onto the surface of the carrier. For example, the grafting reaction mechanism of heptadecafluorodecyltrimethoxysilane and the carrier is as follows: Figure 1 As shown, heptadecafluorodecyltrimethoxysilane first undergoes self-hydrolysis and polymerization, and then undergoes dehydration condensation with hydroxyl groups (-OH) on the surface of the carrier to be grafted onto the surface of the carrier. The result of the grafting reaction of the hydrophobic component on the surface of the carrier can be obtained by, for example, XPS test analysis.
[0063] In some embodiments, the carrier is fished out after impregnation and dried at 80-100° C. The drying may be performed in a manner known to those skilled in the art, and the present invention is not particularly limited thereto.
[0064] The technical solution of the present invention will be further illustrated by specific embodiments below.
[0065] Example
[0066] Example 1
[0067] Step S1: The nickel foam is placed in deionized water and anhydrous ethanol for ultrasonic cleaning for 20 minutes, and then placed in an oven for drying at 60° C. for 1 hour.
[0068] 4g glucose and 4g urea were dissolved in 30ml deionized water, and then the solution and nickel foam were transferred to a Teflon-lined reactor, and the hydrothermal reaction was carried out at 180℃ for 8h. After the reaction, the nickel foam was removed and rinsed with deionized water three times, and dried at 80℃ overnight to obtain a nickel foam support with a nitrogen-doped carbon layer (denoted as NC / FN). The mass of nitrogen-doped carbon (denoted as NC) in NC / FN was weighed by the difference method, KOH was weighed according to the mass ratio of NC to KOH of 1:2, and deionized water was used to prepare a solution so that NC / FN could be immersed in the KOH solution and then placed in an oven for reaction at 120℃ for 12h. After the reaction, NC / FN was placed in a tube furnace and calcined at 700℃ in an argon (Ar) atmosphere for 1h. Finally, NC / FN was rinsed with deionized water, placed in a vacuum oven, and dried at 150℃ for 24h to obtain porous NC / FN.
[0069] Step S2: At room temperature, 5 g of porous NC / FN was immersed in 50 ml of 0.03 mol / L ethanol solution of chloroplatinic acid hexahydrate. After the solvent was completely evaporated, it was placed in an oven to dry, and dried at 70°C for 12 h. Then it was placed in a tubular furnace, and the temperature was raised from room temperature to 220°C at a rate of 10°C / min in an argon atmosphere (flow rate of 500 ml / min). After reaching this temperature, H2 (flow rate of 500 ml / min) was introduced for reduction, and the reduction was carried out at 220°C for 8 h. After the reduction was completed, the introduction of H2 was stopped, and the catalyst was cooled overnight under the protection of Ar (flow rate of 500 ml / min), and finally a platinum-loaded catalyst (denoted as Pt / NC / FN) was obtained.
[0070] Step S3: Pt / NC / FN was completely immersed in a 0.2 wt % ethanol solution of heptadecafluorodecyltrimethoxysilane (FD-TMS) for 12 h, and then taken out and dried at 80° C. for 6 h to obtain a Pt / NC / FN hydrophobic catalyst.
[0071] The catalyst loaded with platinum prepared in step S2 (catalyst before hydrophobic treatment) and the Pt / NC / FN hydrophobic catalyst prepared in step S3 (catalyst after hydrophobic treatment) were subjected to XPS test. The test results are shown in Figure 2 . Figure 2 (a) is the XPS overall spectrum of the catalyst before and after hydrophobic treatment; (b) is the XPS C1s high-resolution energy spectrum of the catalyst before hydrophobic treatment; (c) is the XPS C1s high-resolution energy spectrum of the catalyst after hydrophobic treatment.
[0072] Depend on Figure 2 (a) It can be seen that compared with the catalyst before hydrophobic treatment, the catalyst after hydrophobic treatment with fluorosilane has F KL1 peak and F1s peak, and the C1s fine spectra of the two ( Figure 2As can be seen from (b) and (c), there are only CC and CO related peaks before the hydrophobic treatment, while after the hydrophobic treatment, strong peaks of -CF2- and -CF3 appear. The F element and -CF2- and -CF3 all come from the fluorosilane reagent, which indicates that the fluorosilane is successfully grafted onto the catalyst.
[0073] The performance of the hydrophobic catalyst prepared above was tested according to the following method.
[0074] Static contact angle measurement:
[0075] Use the static contact angle measuring instrument SDC-350 (Dongguan Shengding Precision Instrument Co., Ltd.) to measure. Place the hydrophobic catalyst on the stage of the measuring instrument, move the stage upward to make it contact with the water droplets dripping from the needle tube, and after the two are fully in contact, move the stage downward to make the water droplets leave the needle tube and place them on the hydrophobic catalyst. Use the software that comes with the measuring instrument to fit the contact angle. The larger the static contact angle, the better the hydrophobic performance of the catalyst.
[0076] Measurement of catalytic activity:
[0077] The catalytic activity was tested using a gas-liquid co-current device made in the laboratory. The device mainly consists of a packing column, a catalytic column, and a condenser. The deuterated water (D2O) liquid is converted into D2O saturated vapor in the packing column. The D2O saturated vapor enters the catalytic column together with hydrogen, and a water-hydrogen exchange reaction occurs on the catalyst. Part of the gas after the reaction is condensed into liquid and collected, and the other part of the uncondensed gas is also collected. A density meter is used to measure the deuterium (D) density in the liquid after the reaction and calculate its abundance. A mass spectrometer is used to measure the D abundance in the gas after the reaction. The total volume mass transfer coefficient (Kya) is used to characterize the catalytic activity of the catalyst, and the calculation method is as follows:
[0078]
[0079] Wherein, F in formula (1) is the column efficiency of the catalytic column, y is the deuterium abundance in the gas phase after the reaction, y0 is the deuterium abundance in the gas phase before the reaction, and y ∞ is the deuterium abundance in the gas phase when equilibrium is reached; x in formula (2) ∞ In order to achieve the deuterium abundance in the liquid phase at equilibrium, the reaction temperature of the activity test was 60°C, at which the separation factor of H / D exchange was 3.134; G in formula (3) is the gas flow rate (m 3 / s), V is the volume of the catalyst bed (m 3 ). The larger the total volume mass transfer coefficient, the higher the catalytic activity of the catalyst.
[0080] The conversion relationship between deuterium density and abundance is:
[0081] The deuterium density measured by the densitometer is ρ
[0082] ρD2O =1.105g / ml
[0083] ρ H2O =0.9985g / ml
[0084]
[0085] Comparative Example 1
[0086] The hydrophobic catalyst was prepared in a similar manner to Example 1, except that in step S1, urea was not added for the hydrothermal reaction.
[0087] The hydrophobic catalysts prepared in Example 1 and Comparative Example 1 were subjected to static contact angle measurement and catalytic activity measurement according to the test method of Example 1. The test results are shown in Table 1.
[0088] Table 1
[0089]
[0090] From the above results, it can be seen that the hydrophobic catalyst obtained by using the nickel foam loaded with nitrogen-doped carbon as a carrier, loading the metal active component and using fluorosilane for hydrophobic treatment in the embodiment of the present invention has good hydrophobic performance and catalytic activity. In contrast, the hydrophobic catalyst prepared by using the nickel foam loaded with carbon as a carrier in Comparative Example 1 has poor catalytic activity.
[0091] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A hydrophobic catalyst for water-hydrogen exchange reaction, characterized in that The hydrophobic catalyst comprises: A carrier, the carrier comprising nickel foam and a nitrogen-doped carbon layer in-situ grown on the surface of the nickel foam, wherein the nitrogen-doped carbon layer has a porous structure; an active component, the active component being supported on the nitrogen-doped carbon layer, the active component comprising Pt; and A hydrophobic component is grafted onto the nitrogen-doped carbon layer, wherein the hydrophobic component comprises fluorosilane.
2. The hydrophobic catalyst according to claim 1, wherein The hydrophobic catalyst includes one or more of the following features: (1) The active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt; (2) The fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane.
3. The hydrophobic catalyst according to claim 1 or 2, wherein Based on the total weight of the carrier, the loading amount of the active component is 0.1wt%-1.0wt%.
4. A method for preparing a hydrophobic catalyst, characterized in that: The method comprises the following steps: S1, placing a solution including a carbon source and a nitrogen source and nickel foam in a reaction kettle, performing a hydrothermal reaction at 120° C.-180° C. for 4 h-18 h, and then mixing with an alkaline solution for activation treatment to obtain a carrier having a nitrogen-doped carbon layer in situ grown on the surface of the nickel foam; S2, impregnating the carrier with a precursor solution of an active component, and performing a reduction reaction after drying to obtain a carrier loaded with an active component, wherein the active component includes Pt; S3, immersing the above-mentioned carrier loaded with active components in a solution containing a hydrophobic component for 12h-24h, taking it out and drying it for 6-12h to obtain the hydrophobic catalyst, wherein the hydrophobic component includes fluorosilane.
5. The preparation method according to claim 4, characterized in that: In step S1, the activation treatment includes reacting with the alkaline solution at 100°C-150°C for 6h-24h, and then calcining at 600°C-800°C for 0.5h-3h in an argon atmosphere.
6. The preparation method according to claim 4 or 5, wherein: The ratio of the mass of the nitrogen-doped carbon layer to the mass of the alkali in the alkali solution is 1:1-1:3; Preferably, the base is selected from one or more of KOH or NaOH.
7. The preparation method according to claim 4 or 5, wherein: In step S1, the carbon source is glucose; the nitrogen source is urea.
8. The preparation method according to claim 4, wherein In step S2, the precursor solution of the active component is selected from an alcohol solution of chloroplatinic acid, an alcohol solution of ferrous chloride and chloroplatinic acid, an alcohol solution of chloroiridic acid and chloroplatinic acid, and an alcohol solution of ruthenium trichloride and chloroplatinic acid, wherein the alcohol is selected from ethanol or ethylene glycol; preferably, the concentration of the precursor solution of the active component is 0.1 mol / L-0.3 mol / L; Further preferably, the active component precursor solution is added in an amount of 0.1-1.0 wt% of the active component loading based on the total weight of the carrier with the in-situ grown nitrogen-doped carbon layer; the active component is selected from one or more of Pt, Fe-doped Pt, Ir-doped Pt, and Ru-doped Pt.
9. The preparation method according to claim 4, wherein: In step S2, the reduction reaction is carried out in an argon atmosphere using hydrogen as a reducing agent. The reaction temperature is 200°C-300°C, and the reaction time is 6h-12h.
10. The preparation method according to claim 4, wherein: In step S3, the solution of the hydrophobic component is an ethanol solution of the hydrophobic component; the concentration of the hydrophobic component solution is 0.1wt%-0.3wt%; Preferably, the fluorosilane is selected from one or more of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, heptadecafluorodecyltriethoxysilane and tridecafluorooctyltriethoxysilane.
Citation Information
Patent Citations
Silicon carbide hydrophobic catalyst and preparation method
CN107930621A
Preparation method of neat hydrophobic catalyst
CN104226311A
Nitrogen-doped carbon-coated cobaltosic oxide nanowire monolithic catalyst and preparation method thereof
CN112536055A
Nitrogen-doped supported nano-catalyst as well as preparation method and application thereof
CN116791128A
Preparation and application of hydrophobic noble metal catalyst for treating high-concentration organic wastewater
CN117563679A